Investigation of Iranian pomegranate cultivars for wound healing components - Mohammad Omidi Ghaleh Mohammadi; Sayid Mahdi Mirghazanfari (PAGEPress Publications, 2019)
One of the most important issues which medical science has been facing is wound healing for the tissue repair with the least complications. In this study, we aimed to isolate, purify and quantitate tannins and phenolic compounds from exocarp and pulp of fruits of Iranian pomegranate cultivars. Our findings demonstrate that the highest amount of tannin extracts from ethanol extract of the black peel exocarp was 201.76 ± 1.93. The highest amount of flavonoids from the ethanol extract of Sweet Alac exocarp was119.69 ± 1.02 as well as antioxidant compounds activity in the exocarp and pulp showed that the highest activity is in the ethanol extract of the black peel was 95.65 ± 3.1. The total phenolic activity indicated that the Sour white peel ethanol extract has the highest phenolic activity 327.05 ± 863. Our data suggest that the ethanol extract of pomegranate exocarp has the higher amounts of tannins and flavonoids, compounds that are known to be beneficial for wound healing. Taken together, these data suggest that compounds isolated from Iranian pomegranate cultivars offer new options for managements of wound healing.